Kinematic Analysis of the Forestry Workers’ Upper Body during Chainsaw Starting Activity - Landekić, Matija; Bačić, Marin; Pandur, Zdravko; Bakarić, Matija; Šporčić, Mario; Nakić, Josipa (Forests, 2023)
The application of various graphic analytical software solutions in the research aimed at designing and determining the ergonomic and biomechanical harmony between forestry workers’ anthropometric measures and their working positions and movements is still scientifically incomplete and largely unexplored in forestry, especially regarding motor manual work with chainsaws. Accordingly, the aim of this research is to numerically represent the general kinematic model of forestry workers’ upper body while starting a chainsaw. The same is determined by using a state-of-the-art motion capture suit with inertial measurement units (IMUs). An additional research aim is to investigate numerical values of the forestry worker kinematic model against the three potentially applicable methods of starting a chainsaw and work experience with a chainsaw. Field data collection was carried out during the spring and summer of 2022 and 2023, and a total of 51 chainsaw workers were sampled in different relief areas. The results of the subject research show that none of the observed methods of starting a chainsaw are entirely safe for the worker, concerning the aspect of MSD development, if the body movements within the working element are performed in an incorrect way. From safety and kinematic aspects, regarding forestry workers’ upper body values, the most neutral work posture (N-pose) is when a worker is using the “between the knees” method. The method “from the ground” can be used as secondary option if the workers are educated in taking the correct position of the upper body, i.e., to practice the rule of hip hinge. With the aim of extending the working ability and working life of forestry workers, interdisciplinary cooperation between occupational medicine, kinesiologists, and forestry experts is needed to create a guide of statodynamic efforts and correct postural movement habits during motor manual work in logging operations.